Early prenatal exposure to suspected endocrine disruptor mixtures is associated with lower IQ at age seven. (January 2020) - Tanner, Eva M.; Hallerbäck, Maria Unenge; Wikström, Sverre; Lindh, Christian; Kiviranta, Hannu; Gennings, Chris; Bornehag, Carl-Gustaf
Graphical abstract: Highlights: Early prenatal exposure to 26 suspected endocrine disruptors was related to lower IQ in children. The endocrine disruptor mixture disproportionately impacted boys. Replacement analogue bisphenol F (BPF), may not be a safer alternative to BPA. Preventing short-lived pollutant exposure among pregnant women may mitigate effects. Abstract: Background: Endocrine disrupting chemicals (EDCs) are xenobiotics with the ability to interfere with hormone action, even at low levels. Prior environmental epidemiology studies link numerous suspected EDCs, including phthalates and bisphenol A (BPA), to adverse neurodevelopmental outcomes. However, results for some chemicals were inconsistent and most assessed one chemical at a time. Objectives: To evaluate the overall impact of prenatal exposure to an EDC mixture on neurodevelopment in school-aged children, and identify chemicals of concern while accounting for co-exposures. Methods: Among 718 mother-child pairs from the Swedish Environmental Longitudinal, Mother and child, Asthma and allergy study (SELMA) study, we used Weighted Quantile Sum (WQS) regression to assess the association between 26 EDCs measured in 1st trimester urine or blood, with Wechsler Intelligence Scale for Children (IV) Intelligence Quotient (IQ) scores at age 7 years. Models were adjusted for child sex, gestational age, mother's education, mother's IQ (RAVEN), weight, and smoking status. To evaluate generalizability, we conducted repeated holdout validation, a machine learning technique. Results: Using repeated holdout validation, IQ scores were 1.9-points (CI = −3.6, −0.2) lower among boys for an inter-quartile-range (IQR) change in the WQS index. BPF made the largest contribution to the index with a weight of 14%. Other chemicals of concern and their weights included PBA (9%), TCP (9%), MEP (6%), MBzP (4%), PFOA (6%), PFOS (5%), PFHxS (4%), Triclosan (5%), and BPA (4%). While we did observe an inverse association between EDCs and IQ among all children when training and testing the WQS index estimate on the full dataset, these results were not robust to repeated holdout validation. Conclusion: Among boys, early prenatal exposure to EDCs was associated with lower intellectual functioning at age 7. We identified bisphenol F as the primary chemical of concern, suggesting that the BPA replacement compound may not be any safer for children. Future studies are needed to confirm the potential neurotoxicity of replacement analogues.